Magnetospheric Multiscale observations of large‐amplitude, parallel, electrostatic waves associated with magnetic reconnection at the magnetopause - R. E. Ergun; J. C. Holmes; K. A. Goodrich; Victoria Wilder; J. E Stawarz; S. Eriksson; D. L. Newman; S. J. Schwartz; M. V. Goldman; A. P. Sturner; D. M. Malaspina; M. E. Usanova; et al. (Geophysical Research Letters)
Abstract We report observations from the Magnetospheric Multiscale satellites of large‐amplitude, parallel, electrostatic waves associated with magnetic reconnection at the Earth's magnetopause. The observed waves have parallel electric fields (E||) with amplitudes on the order of 100 mV/m and display nonlinear characteristics that suggest a possible net E||. These waves are observed within the ion diffusion region and adjacent to (within several electron skin depths) the electron diffusion region. They are in or near the magnetosphere side current layer. Simulation results support that the strong electrostatic linear and nonlinear wave activities appear to be driven by a two stream instability, which is a consequence of mixing cold (<10 eV) plasma in the magnetosphere with warm (~100 eV) plasma from the magnetosheath on a freshly reconnected magnetic field line. The frequent observation of these waves suggests that cold plasma is often present near the magnetopause.